2023
DOI: 10.3389/fpubh.2023.1243213
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability status at rest in adult depressed patients: a systematic review and meta-analysis

Qianqian Wu,
Xiangyang Miao,
Yingying Cao
et al.

Abstract: PurposesA meta-analysis was conducted to examine the differences in heart rate variability (HRV) between depressed patients and healthy individuals, with the purpose of providing a theoretical basis for the diagnosis of depression and the prevention of cardiovascular diseases.MethodsTo search China National Knowledge Infrastructure (CNKI), WanFang, VIP, PubMed, Web of Science, Science Direct, and Cochrane Library databases to collect case–control studies on HRV in depressed patients, the retrieval date is from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…These results align with Borrione et al’s [ 32 ] findings, which demonstrated a negative correlation between depressive symptoms and LF of HRV and a positive correlation with the LF/HF ratio. These data suggest vagal withdrawal in patients with MDD [ 14 , 17 , 19 ]. Additionally, the HRV indices demonstrated a decline with age in both the MDD and HC groups [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These results align with Borrione et al’s [ 32 ] findings, which demonstrated a negative correlation between depressive symptoms and LF of HRV and a positive correlation with the LF/HF ratio. These data suggest vagal withdrawal in patients with MDD [ 14 , 17 , 19 ]. Additionally, the HRV indices demonstrated a decline with age in both the MDD and HC groups [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
“…Porges [ 14 ] proposed the polyvagal theory to elucidate the complex interplay between cardiac autonomic function, emotional regulation, and social interaction behavior. Previous studies demonstrated that patients with MDD exhibited diminished vagal modulation at rest [ 15 , 16 , 17 , 18 , 19 ] as well as during laboratory-induced emotion tasks, such as viewing sad films. A meta-analysis involving 43 studies encompassing 2359 patients with depression and 3547 healthy controls revealed that patients with depression had lower HRV indices (SDNN, RMSSD, pNN50, LF, and HF) compared to the healthy controls; however, no significant difference was observed in the LF/HF ratio between the two groups [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation